Measures to Improve Zooveterinary Services on Livestock Farms and Locate Livestock - Tygalov B.A; Qulmonov Bekzod Pirnazarovich; Ibrohimov I.; Mirov U; Toshpulatov M (Peerian Journals Publishing, 2022)
The article discusses the issues of landscaping around livestock, creating a quality fodder base, the construction of buildings, barns, veterinary and sanitary requirements for dairy cows
Keywords: Farms; milk,; cattle; microclimate